Sosialisasi Upaya Penanggulangan Dengan Tindak Pidana Pencurian yang Dilakukan Secara Bersama Sama Dalam Modus Memecahkan Kaca Mobil - Karina, Ica; Siahaan, Ade Yuliany; F, Fitriani (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The purpose of this study was to find out the modus operandi of the perpetrators of the crime of theft which were carried out jointly by breaking the windshield and countermeasures against the crime of theft which were carried out jointly by breaking the windshield. This research is descriptive in nature. The data used in this research are primary data and secondary data. Secondary data is data that uses information or supports the completeness of primary data. Secondary data was obtained by studying documents by reading, studying and analyzing literature in the form of laws and regulations, books and other sources related to this research. The results of the study show that the modus operandi of the perpetrators of the crime of theft which are carried out jointly with the modus operandi of breaking car windows is by breaking the keyhole, breaking the glass, making fake keys, or in other more neat ways. It is the duty of the police to study the new modes that are carried out by the perpetrators of theft with the mode of breaking the windshield in order to complete the disclosure of cases or maybe even be able to anticipate a crime in the future and efforts to overcome the conspiracy of criminal acts of theft with the mode of breaking the glass of the car are carried out various efforts such as Pre-Emtive efforts, namely by making banners or billboards in public places that require CCTV to be made so that if a crime occurs it can help the police conduct investigations, as well as carry out Preventive efforts, namely carrying out scheduled and continuing operations or mobile raids and carrying o ut cooperation between parties police with an institution or agency and appealed to the public to be more vigilant and not leave valuables in the car.